New Method Using Sedimentation and Immunomagnetic Separation for Isolation and Enumeration of Cryptosporidium parvum Oocysts and Giardia lamblia cysts - Massanet-Nicolau, Jaime (American Society for Microbiology, 2003)
A new method for the isolation of Cryptosporidium parvum oocysts and Giardia lamblia cysts from biosolid samples has been developed that utilizes sedimentation and immunomagnetic separation. The method was used to recover stained cysts and oocysts (spike organisms) from primary settled sewage sludge, anaerobically digested sewage sludge, and bovine manure. Recovery efficiencies associated with this method were approximately 40 to 60% and were significantly greater than those associated with similar methods based on sucrose flotation (P < 0.001). The recovery efficiency of the sedimentation-based method showed no significant reduction as a result of sample storage for up to 21 days (P > 0.05). Recovery efficiencies were determined by spiking samples with prestained cysts and oocysts, allowing them to be differentiated from those naturally present in the biosolid samples. The prestained cysts and oocysts had been fixed in 5% formalin, and the recovery efficiencies associated with this method may be different from recovery efficiencies for fresh cysts or oocysts.